Ofiara zwierzęca w obrzędowości starożytnych Rzymian: rekonstrukcja rytuału ofiarnego w świetle antycznych świadectw literackich - Kaczor, Idaliana (Collectanea Philologica, 2021)
Religious ceremonies in ancient Rome, foundational for its cult, made manifest the communal piety by the means of sacrificial rites. Adopting a formalist religious approach, the Romans carefully regulated the sacrificial process (sacrificium). Partially preserved literary sources in theory allow one to reconstruct the sequence of acts comprising a Roman sacrificial rite, with the following article employing said sources to propose a template for a Roman animal sacrifice ritual.